Editorial: Recent trends in the publishing profile of Forest Ecology and Management - Binkley, Dan; Cook, Rachel; Fernandez, María Elena; Kouki, Jari; Ribeiro, Natasha (Elsevier, 2024)
Advancements in forest science are shared with the community in peer-reviewed articles, and forest science is the domain of more than a dozen mainstream journals around the world. As knowledge and understanding evolve over time, so do our journals. In North America, Forest Science was launched by the Society of American Foresters in 1955, followed 16 years later by the Canadian Journal of Forest Research from the federal government. These journals were preceded by a variety of European journals. Annals of Forest Science traces back to 1923, originally published by the French National School of Water and Forests. The European Journal of Forest Research has an even longer history, originating in 1857 as the “Monthly magazine for forestry and hunting with a special focus on southern Germany.” All of these journals were produced by professional societies and government agencies. A new model appeared in 1976, when Forest Ecology and Management was launched to provide an international forum for forest science. This journal was published by a commercial enterprise, supported by subscriptions paid by individuals and institutions with no “page charges” to authors. Journal publishing continued to evolve, including a shift from print to digital media, a growing emphasis on open access (including several new journals, supported by fees paid by authors) and a shift to platforms hosted by commercial publishers for all journals.